2020
DOI: 10.1111/jace.17317
|View full text |Cite
|
Sign up to set email alerts
|

CVD synthesis and characterization of thin Mo2C crystals

Abstract: In this study, we present an investigation on the growth of thin Mo2C crystals via chemical vapor deposition using CH4. Optical microscopy (OM), scanning electron microscopy (SEM), atomic force microscopy(AFM), and Raman spectroscopy studies show that the morphology and the thickness of Mo2C crystals are strongly affected by the impurities in the system, the thickness of the copper substrate, and the graphene presence on Cu surface prior to Mo2C formation. Our studies show that during the CVD process, orthorho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 39 publications
3
39
0
Order By: Relevance
“…4 that as the amount of In (layer thickness) increases, the thickness of the Mo 2 C crystals decreases. This is also in agreement with previous studies performed with Cu 7 9 .…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…4 that as the amount of In (layer thickness) increases, the thickness of the Mo 2 C crystals decreases. This is also in agreement with previous studies performed with Cu 7 9 .…”
Section: Resultssupporting
confidence: 94%
“…3 b), which were obtained from the crystals in both regions (under carbon thin film and on bare In surface), confirmed that the grown crystals are Mo 2 C and the thin film is mostly amorphous carbon. The crystal structure of the Mo 2 C crystals is investigated and through Raman Spectroscopy analysis 9 (Raman peaks at ∼ 231, and 656 cm −1 ), XRD (2 theta at 38° and 69°) and TEM (Fig. 3 g) studies it is found to be orthorhombic which also agrees well with literature 6 , 8 10 , 12 , 13 , 15 , 18 – 23 .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…4 At high partial pressures of CH 4 , graphene is also formed on the Cu surface, in addition to Mo 2 C crystals, resulting in graphene/Mo 2 C heterostructures [6][7][8][9][10][11][12] or even graphene/Mo 2 C/graphene sandwich structures. 13 The usual CVD parameters, such as the growth temperature, duration, and gas flow rates (CH 4 and H 2 ), have been shown to significantly impact the final outcome in terms of the morphology and thickness of Mo 2 C, and the formation of graphene along with Mo 2 C. [5][6][7][10][11][12] In addition to the parameters of the gas phase, it is expected that condensed phases of the system also have pivotal affects for the process and resulting structure of materials. It has been postulated 5 that the thickness of the Cu substrate affects the morphology and thickness of the Mo 2 C crystals significantly by altering diffusion path length of Mo but details of the process are not known.…”
Section: Introductionmentioning
confidence: 99%
“…With the purpose of controlling the morphology of the crystals, various groups have successfully studied the effects of various processing parameters such as the thickness of Cu foil [7][8][9] , CH4:H2 ratio 6,8,[10][11][12][13] , and duration 6,8,[10][11][12]14 . Although temperature is a very critical processing parameter, in this process the choice of temperature is very limited (above 1085 C) because Cu must be in the liquid state to allow the diffusion of Mo atoms through Cu towards the surface.…”
Section: Results Is the Formation Of 2mo + C  Mo2cmentioning
confidence: 99%